Kajian Dampak Alih Fungsi Terhadap Perubahan Fasad Bangunan Bioskop Ria Pematangsiantar - Cahyani, Retno; Fahrizal, Effan; Novianti, Yenny (Rifa'Institute, 2023)
Ria Cinema is located in Pematangsiantar City. This cinema was built in 1953 and started operating actively in 1955. This building is a cinema building that was built after the end of the Dutch occupation of Indonesia. In 2003, this cinema was no longer actively operating. The main reason is because the cinema does not support the city's economy, in 2022 the former cinema building has been restored and revived by changing its function as a food court which is named Foodcourt Ria Heritage. Transfer of function is the process of an activity that changes the initial function into a new function of a room, a building. Transfer of building functions is a strategy in building preservation. As a historical relic in the field of film, the existence of this building certainly has a lot of potential. This study discusses the description of the changes in the building of the former Ria Cinema in terms of building facades and spatial planning. This study uses a qualitative method with a descriptive approach that aims to describe the observed object. In this study it was found that the conversion of the former Ria cinema building was determined by several elements, namely the facade elements (walls, doors, windows, roof and structures) and spatial elements. This research concludes that the conversion of the former Ria cinema building into a Ria Heritage food court has affected the change in facade elements